Nonlinear models for describing development and fecundity of the pseudococcid predators Nephus includens and Nephus bisignatus - Kontodimas, Dimitrios Ch. (ENTOMOLOGIA HELLENICA, 2012)
Among several mathematical models used to describe the development or the fecundity of insects the equations of Enkegaard, Analytis, Bieri 1 and Bieri 2 could describe both biological features. In the current study these equations used to describe the development and fecundity of two pseudococcid predators [Nephus includens (Kirsch) and Nephus bisignatus (Boheman) (Coleoptera: Coccinellidae)] preying on Planococcus citri (Risso) (Hemiptera: Pseudococcidae) at constant temperatures (15oC - 35oC). All models have goodness of fit to data especially for development [R2 adj, RSS and AIC ranged 0.9908-0.9996, 0.0019-89.1752 (x10-4), and (-75.43) – (-31.07) respectively]. Optimum temperature (Topt) and upper threshold (Tmax) were calculated accurately by all models (Topt ranged 32.6-34.0oC for N. includens and 30.0-30.6oC for N. bisignatus and Tmax ranged 35.0-38.8oC for N. includens and 33.1-36.0oC for N. bisignatus, respectively). Lower temperature threshold (Tmin) was calculated accurately by Bieri-1 model (11.0 and 10.0oC for N. includens and N. bisignatus respectively) whereas Analytis model underestimated it (8.0 and 4.9oC). As far as fecundity is concerned the respective values were better fitted near the optimum temperature (25oC) [R2 adj, RSS and AIC ranged 0.8246-0.9704, 9.2729-24.0736 and (-246.82) – (-115.34) respectively]. Conclusively, from the tested models the Bieri-1 equation was proved as the most appropriate for the reason that could estimate correctly all the requested parameters concerning the development (Tmin, Topt, Tmax) as well as it could describe sufficiently the fecundity trend of the two predators.